Sudden Hemianopsia Secondary to Ethmoid Sinus Mucocele - Morganti, Ligia; Evangelista, Leandro; Guimaraes, Roberto; Crosara, Paulo (International Archives of Otorhinolaryngology, 2014)
Paranasal sinus mucoceles are benign cystic lesions, filled with mucus, occurring due to an obstruction of involved sinus ostium. They are indolent, locally expansive, and destructive. Surgical treatment must be performed and, when done at the correct time, may prevent sequelae. We present a case of ethmoid sinus mucocele with orbit involvement and permanent optical nerve injury.
Keywords: ethmoid sinus; sinus mucocele; hemianopsia